Cixous after / Depuis 2000 - Hall, Elizabeth Berglund (BRILL, 2017)
The essays in Cixous after/depuis 2000, edited by Hall, Chevillot, Hoft-March, and Peñalver Vicea, focus on Hélène Cixous's work of the 21st-century, exploring her treatment of mourning, suffering and death in the wake of events that mark her life from 2000-2015. Les essais réunis dans Cixous après/depuis 2000, sous la direction de Hall, Chevillot, Hoft-March et Peñalver Vicea, considèrent les textes d'Hélène Cixous publiés au 21e siècle ; ils explorent également les questionnements de l'écrivaine sur le deuil, la souffrance et la mort dans le sillage des événements qui ont marqué sa vie entre 2000 et 2015
Description based on publisher supplied metadata and other sources